PENYERLAHAN PEMIKIRAN DAN IDENTITI PENUTUR KESAN PENYINGKATAN/ PELEMAHAN KATA BAHASA LISAN - Isam, Hishamudin; Mutalib, Mashetoh Abd.; Zain, Norwati Mohd. (Jurnal Pendidikan Bahasa dan Sastra, 2014)
This study, specifically aims to examine the phenomenon of clipped or attenuated words which often takes place in the spoken language. Data for the study were collected from 20 personal blogs of two groups of gender with different sexual orientations (men and gays) selected randomly from blogspot.com from 2009 to 2012. The data were analyzed using semantic prosody as the theoretical approach. New information was extracted from the analysis ofthe clipping or attenuation of the word â€œnak.â€The findings reveal that the two groups have their own ways of expressing the sense of 'desire' which is realized through the use of the word â€œnakâ€Â  by men and gay speakers based on their expression ofÂ  three (3) main 'desires', namely orientation (sexual, financial), intent (good intention, work, marriage) and feeling (faithfulness, laziness). This situation clearly demonstrates that the phenomenon of the use of language mediates the expressions of outburst, concerns, hopes, and aspirations of gender and transgender groups to the extent that both their thoughtsand identities can be detected by the readers.